Hit the right target! The Role of Issue Saliency among a Party's Potential Voters as a Determinant of the Party's Issue Emphasis in Switzerland. Issue 2 (10th March 2022) - Borgeat, Quentin
Abstract: Issues matter in party competition. Therefore, the issue emphasis strategy of parties plays an important role during a campaign. Scholars disagree about the factors that explain strategies. Some argue that parties "ride‐the‐wave" and emphasize issues that are important for the public. Others argue that parties care about the issue priorities of their voters. Between these two theories, I argue that parties care about their potential voters, which means that issue priorities among potential voters have an impact on the issue emphasis of parties. The more important an issue is among this group, the more a party will emphasize this issue. To test this hypothesis, I use the panel survey of the Swiss Election Study Selects and the Année Politique Suisse data on newspaper ads. The findings from a multilevel zero‐inflated negative binomial regression suggest that the issue saliency among the potential voters has a positive impact on the issue emphasis of parties. Zusammenfassung: Im Parteienwettbewerb spielen Themen eine Rolle. Daher ist die strategische Hervorhebung bestimmter Themen durch Parteien in Wahlkämpfen von zentraler Bedeutung. Unklar ist allerdings, welche Faktoren diese Strategien erklären. Einerseits wird oft argumentiert, dass die Parteien diejenigen Themen betonen, die der Öffentlichkeit wichtig sind. Andere argumentieren, dass Parteien den prioritären Themen ihrer Wähler besondere Beachtung schenken. Dieser Beitrag argumentiert, dass Parteien sich um ihre potenziellen Wähler kümmern und die Themenprioritäten dieser Gruppe besonders berücksichtigen. Diese Hypothese wird mithilfe der Panelerhebung der Schweizer Wahlstudie Selects und den Daten der Année Politique Suisse zu Zeitungsanzeigen getestet. Die Ergebnisse einer mehrstufigen zero‐inflated negativen Binomialregression deuten darauf hin, dass die Bedeutung bestimmter Themen für die potenziellen Wähler die Themenbetonung der Parteien positiv beeinflusst. Résumé: La compétition partisane se centre sur les enjeux. Par conséquent, la stratégie des partis vis‐à‐vis des enjeux joue un rôle important pendant les campagnes. Il n'existe pas de consensus concernant les facteurs influençant ces stratégies. Certains affirment que les partis suivent la vague en concentrant leur attention sur les enjeux les plus importants pour l'électorat en général. D'autres argumentent que les partis se concentrent sur les priorités de leurs électeurs. Pour ma part, j'argumente que les partis prennent en considération leurs électeurs potentiels. Plus un enjeu est important pour ces électeurs potentiels, plus un parti va concentrer son attention sur cet enjeu. Pour tester cette hypothèse, j'utilise les données panels de l'Étude Électorale Suisse (Selects) et les données relatives aux publicités dans les journaux d'Année Politique Suisse. Les résultats de ma régression multiniveaux binomiale négative avec excès de zéros suggèrent que les priorités des électeurs potentiels ont une influence positive sur les stratégies des partis en terme d'enjeux.